Menopausal dyslipoproteinemia in breast carcinoma patients: a laboratory analysis - Narkhede, Harshal P.; Muddeshwar, Manohar G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Seldom any precedent work has aimed to study the influence of age and menopausal status towards serum lipoproteins levels in breast cancer. Owing to influence of sex-steroids over lipid handling by oestrogen-dependent breast cells, their serum levels might reveal insinuating facts, if menopausal status-wise analysis is attempted. Ascertainment of serum lipid/lipoprotein aberrations in breast carcinoma; and substantiation of their behaviour with age and menopause among breast cancer and healthy subjects. Methods: Laboratory analyses of serum total cholesterol (TC), high density lipoprotein cholesterol (HDL-c), low and very low density lipoproteins (LDL-c, VLDL-c) and triglycerides (TG) were done among breast cancer subjects (n=50) and healthy women (n=50) with respect to their age (3 sub-groups viz. 25-40, 41-55 and 56-75 years) and menopausal status. Grouped numerical data were subjected to intra- and inter-group comparisons using Student’s unpaired-‘t’-test and ANOVA with Post-Hoc comparisons using Tukey-HSD (Honestly-Significant-Difference) Test. Results: Higher serum LDL-c and TC with lower HDL-c levels were observed among breast carcinoma subjects than healthy women (P=0.004, 0.003, 0.009 respectively). Serum LDL-c elevation in peri- and post-menopausal age (P=0.009), while lowered HDL-c specifically during post-menopausal age (0.004) were significantly evident in breast cancer subjects. Conclusions: Breast carcinoma has obvious alliance with serum LDL-c, TC and HDL-c aberrations. LDL-c has specific variability during peri-menopausal and post-menopausal ages among breast cancer subjects. HDL-c alteration is mainly concerted for post-menopausal age; while total cholesterol could be a peril throughout. The odds of pooled effect of such aberrations in cancer causation cannot be underrated.